2011
DOI: 10.1111/j.1651-2227.2011.02191.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose thiazide diuretics in children with idiopathic renal hypercalciuria

Abstract: Our results suggest that low dose (0.5 mg/kg/day) of hydrochlorothiazide may be safe and effective in controlling renal hypercalciuria in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
7
1
1
Order By: Relevance
“…In our study, although we did not use placebo drug, most patients that were treated with cystone reported passage of stone and the size of stones decreased in ultrasound that was consistent with the results of the previous studies. Some previous studies have shown that hydrochlorothiazide is a treatment for some type of hypercalciuria that helps prevention and treatment of urinary stones, which is not consistent with the findings of the present study (16,19). Yosefi et al conducted a study on the effects of hydrochlorothiazide on prevention of recurrent urinary tract infections in children with idiopathic hypercalciuria.…”
Section: Discussioncontrasting
confidence: 95%
“…In our study, although we did not use placebo drug, most patients that were treated with cystone reported passage of stone and the size of stones decreased in ultrasound that was consistent with the results of the previous studies. Some previous studies have shown that hydrochlorothiazide is a treatment for some type of hypercalciuria that helps prevention and treatment of urinary stones, which is not consistent with the findings of the present study (16,19). Yosefi et al conducted a study on the effects of hydrochlorothiazide on prevention of recurrent urinary tract infections in children with idiopathic hypercalciuria.…”
Section: Discussioncontrasting
confidence: 95%
“…This hypothesis is supported by the observation that 24-hour urine volume increased on subsequent urine analyses. An alternative explanation is that assessing urine chemistries identifies specific metabolic abnormalities that could be treated with targeted therapy, such as lemonade or citrate for patients with hypocitraturia 21 and thiazides for patients with hypercalciuria 2226 However, in successful clinical trials of adult participants, only 22% treated with citrate and 47% of those treated with thiazides met pre-specified cut points for hypocitraturia and hypercalciuria, respectively. 23 Our study highlights the need for well-designed randomized trials to test the efficacy of targeted PPT on stone recurrence among children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the effect of thiazide diuretics in enhancing calcium reabsorption, these diuretics are used frequently in the setting of inherited forms of hypercalciuria in children (99). Rigorous studies investigating the effectiveness of thiazide diuretics alone or in combination in the pediatric cardiac population do not exist, yet anecdotal experience indicates efficacy in the acute setting.…”
Section: Thiazide Diureticsmentioning
confidence: 98%